Bolivian Oil and Natural Gas under State and Private Control, 1910-2010 - Herbert S. Klein; José Alejandro Peres-Cajías (Bolivian Studies Journal, 2014)
Since the 1920 discovery of oil in Bolivia, the country has experimented with varying systems of private control, monopoly state ownership and even mixed state and private ownership/rental of petroleum and gas fields. The aim of our analysis is to explain why these varying patterns of ownership occurred over time and to describe how they affected production in this industry. The analysis suggests that nationalizations have been successful insofar as they took advantage of previous private investment which, meanwhile, underscores the success of the legislation for opening up access to attract private investment. This relative success of the different legal frameworks permits us to understand why the state has been changing from one scheme to another over time. Some partial explanations are offered in order to understand why these schemes could succeed with such regularity. Desde el descubrimiento del petróleo en Bolivia en el año 1920, el país ha experimentado con una variedad de sistemas de control privado, de propiedad monopólica estatal e incluso con la propiedad o el alquiler de campos petroleros y de gas en manos privadas. El propósito de nuestro análisis es explicar por qué se han dado estos variados modelos de propiedad y describir cómo han afectado en la producción de esta industria. El análisis sugiere que las nacionalizaciones han sido exitosas en la medida en que tomaron ventaja de una inversión privada anterior, lo cual mientras tanto resalta el éxito de la legislación de “apertura” para atraer la inversión privada. El éxito relativo de los diferentes marcos legales nos permite comprender por qué el estado ha ido cambiando de un esquema a otro con el paso del tiempo. Se ofrecen algunas explicaciones parciales para entender por qué este esquema pudo dar resultado con tanta regularidad.